2011
DOI: 10.1097/aln.0b013e318219d734
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Surgical Apgar Score across All Surgical Subspecialties as a Means to Predict Postoperative Mortality

Abstract: Background: A surgical scoring system, akin to the obstetrician's Apgar score, has been developed to assess postoperative risk. To date, evaluation of this scoring system has been limited to general and vascular services. The authors attempt to externally validate and expand the Surgical Apgar Score across a wide breadth of surgical subspecialties. Methods: Intraoperative data for 123,864 procedures including all surgical subspecialties were collected and associated with Surgical Apgar Scores (created by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 19 publications
6
69
1
2
Order By: Relevance
“…Patients who are scheduled for radical prostatectomy are generally in a better health condition compared to patients who undergo radical cystectomy or renal mass excision. Our finding might be supported by an analysis [14] of 123,864 surgical procedures that showed that patients who underwent a urologic procedure had a weaker association of SAS and the probability to die within 7 days after surgery. The mortality rate of the latter study and our study (0.5 and 0.1% at 30 days, respectively) are comparable.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Patients who are scheduled for radical prostatectomy are generally in a better health condition compared to patients who undergo radical cystectomy or renal mass excision. Our finding might be supported by an analysis [14] of 123,864 surgical procedures that showed that patients who underwent a urologic procedure had a weaker association of SAS and the probability to die within 7 days after surgery. The mortality rate of the latter study and our study (0.5 and 0.1% at 30 days, respectively) are comparable.…”
Section: Discussionsupporting
confidence: 67%
“…In vascular or trauma surgery, intraoperative tachycardia and hypotension are encountered more frequently and are associated with a poorer outcome. This may explain the better fit of the SAS as a predictor for mortality and high-grade PAE in these patient collectives [6,14] . Our patients were screened preoperatively through electrocardiogram, exercise electrocardiogram and the pulmonary function test to identify obvious cardio-pulmonal morbidity, which is considered a contraindication for radical prostatectomy, and the exclusion of patients with serious cardiac comorbidity might result in presumably more stable hemodynamic conditions indicated by higher SAS scores intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…3 Renal comorbidity included history of acute or chronic renal disease. 4 Coagulation comorbidity comprised hereditary and acquired coagulation disorder, as well as the use of anticoagulation agents such as warfarin, acetylsalicylic acid and clopidogrel. …”
Section: Resultsmentioning
confidence: 99%
“…Likewise they are the second capital cause of the hospitalization increasing the postoperative complications and mortality rate of these patients for a shortterm (30-days) and mid-term (6-months) period as well (2,3). According to the studies the novel 10-point Surgical Apgar Score (SAS) has been considered as a good independent predictor of the major postoperative complications and mortality within a period of 30-days after surgery among many surgical subspecialities (4). It is an easy calculated, simple, objective, real-time parameter computed as a sum of the three vital intraoperative variables.…”
Section: Introductionmentioning
confidence: 99%
“…This 10-point score, which allows risk stratification in the postoperative setting, is based on three variables: the estimated blood loss (EBL), lowest heart rate (HR) and lowest mean arterial pressure (MAP) during surgery (Table 1). This score has been demonstrated to be a good predictor of the occurrence of major complications or death within 30 days of surgery; a high score is associated with a low risk of postoperative major complications or death, while a low score is associated with an increased risk [2,8,10].…”
Section: Introductionmentioning
confidence: 99%